Clinical efficacy evaluation of pedicled vascularized iliac bone graft transfer for osteonecrosis of the femoral head: a retrospective study with DCE-MRI/CTP analysis - Zhang, Tianchen; Zheng, Shanbin; Zhai, Yuyang; Hou, Xinyi; Wang, Yawen; Chen, Zhiyuan; Cao, Xun; Xia, Zilei; Xia, Tianwei; Shen, Jirong (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the clinical efficacy of pedicled vascularized iliac bone graft transfer (PVIBGT) in treating osteonecrosis of the femoral head (ONFH) at Association Research Circulation Osseous (ARCO) stages II–IIIB, to assess postoperative revascularization using standardized dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and CT perfusion imaging (CTP), and to identify independent predictors of surgical success through multivariate analysis.MethodsA retrospective analysis was conducted on 50 patients (51 hips) with ARCO stage II–IIIB ONFH (aged 18–48 years) who underwent PVIBGT between March 2021 and November 2024. Functional outcomes were assessed using Harris score. Radiographic evaluations (x-ray, CT) were used to assess bone graft integration and femoral head morphology. DCE-MRI parameters (IAUGC, CER, MaxSlope, Ktrans, Kep, Ve) and postoperative CTP indices (BF, BV, MTT) were used to quantify perfusion and microcirculatory status. Multivariate binary logistic regression including ARCO stage, etiology, age, sex, disease duration, and graft dimensions (length, diameter) was performed to identify independent predictors of hip-preservation success. Analyses were conducted using SPSS 26.0.ResultsThe mean follow-up duration was 15.1 months. Harris score improved significantly from a preoperative value of 62.39 ± 6.73 (median = 64.00, interquartile range = 10.00) to a postoperative value of 81.88 ± 10.20 (median = 85.00, interquartile range = 9.00) (P < 0.001). The clinical success rate was 80.39% (41/51 hips), and the radiographic success rate was 70.59% (36/51 hips). Logistic regression revealed no independent predictors among etiology, ARCO stage, sex, age, disease duration, or graft dimensions (P > 0.05). DCE-MRI showed partial normalization of perfusion in the femoral head, while CTP indicated favorable hemodynamic status in the operated hip. Ten hips (19.61%) required THA due to femoral head collapse (>2 mm, 6 cases), joint space narrowing with persistent pain (3 cases), or poor function (1 case).ConclusionPVIBGT effectively improves hip function and delays femoral head collapse in ARCO II–IIIB ONFH. Combined DCE-MRI and CTP provide objective imaging evidence for postoperative revascularization assessment. No single factor independently predicted success, possibly due to limited sample size and subgroup heterogeneity. Larger, prospective multicenter studies with standardized imaging protocols and extended follow-up are warranted to confirm these findings.